Optimization of the Family in the Treatment of DM and Gangrene With Herbal Therapy - Lilis Setyowati; Nur Aini; Erma Wahyu Mas; Ollyvia Freeska Dwi Marta; Diah Laila Zulva (PT FORMOSA CENDEKIA GLOBAL, 2023)
Diabetes Mellitus (DM) is a chronic disease with a high incidence in almost all countries. Diabetes Self-Management Education (DSME) is a health education process for individuals and families managing DM patients. The solution provided through this engagement is applying the DSME method to partners by applying for the program: 1. Assistance on DM material, diet planning, signs and symptoms, and how to handle hypo and hyperglycemia conditions; 2. Utilizing local plants as herbal therapy; 3. Training on treating gangrene wounds with the wisdom of herbal therapy using turmeric and betel leaves. The observation was for six months, and intervention was given for one month. The results of the monitoring family can provide and serve food for families with DM, there is no gangrene wound, and they can apply gangrene wound treatment using turmeric and betel leaf herbs.